Perceptions and Experiences of Self-Management in Patients with Prediabetes: A Qualitative Study in China - Jiang J; Feng Q; Yan L; Guo Y; Yang Q (Patient Preference and Adherence)
Jinfeng Jiang,1 Qiongyao Feng,2 Lihua Yan,2 Yingchao Guo,2 Qiu Yang1 1Endocrinology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of China; 2Faculty of Nursing, North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of ChinaCorrespondence: Qiu Yang, Endocrinology, Affiliated Hospital of North Sichuan Medical College, No. 1, Maoyuan South Road, Shunqing District, Nanchong City, Sichuan Province, People’s Republic of China, Tel +86-13990801043, Email yang0hao123@163.comPurpose: This study aimed to investigate self-management experiences among individuals with prediabetes and analyze their potential self-management needs, thereby informing strategies to enhance self-management efficacy and facilitate the development of evidence-based, personalized interventions.Patients and Methods: Twelve prediabetes patients from a physical examination center in Nanchong, China, were recruited using purposive sampling. An interpretive phenomenological research method was employed. Semi-structured, in-depth interviews were conducted to explore patients’ self-management experiences. The interviews were audio-recorded, transcribed, and analyzed thematically to develop the results. In addition, web-based information support and peer support facilitated patient self-management.Results: Four overarching themes emerged: (1) cognitive limitations, (2) intrinsic motivation, (3) hurdles to overcome, (4) perceived social support. Revealed the debilitating effect of non-medical terminology expression on the potential harm of the disease, neglect of diagnosis and health education by healthcare providers exacerbated the lack of awareness of prediabetes among patients. The complex social environment (unhealthy food environment, heavy work pressure, etc.) confronts prediabetes with self-management dilemmas. It was also revealed that patients’ behavioral change motivation was “threat-benefit” dual-driven and was strongly influenced by family ethics, with family culture significantly influencing health decision-making. In addition, web-based information support and peer support facilitate patient self-management.Conclusion: This study investigated the perceptions and self-management experiences of individuals with prediabetes, proposing targeted intervention strategies. Key recommendations include: (1) Healthcare providers’ perceptions and attitudes toward prediabetes significantly influence patient engagement, necessitating standardized diagnostic and treatment protocols that emphasize disease progression risks during initial diagnosis to enhance clinical awareness; (2) Implementation of motivational interviewing (MI) techniques could effectively strengthen patients’ intrinsic motivation for behavioral modification; (3) Multidimensional support systems should be established through AI-powered medical question-answering systems, standardized nutritional labeling regulations, family-involved health education programs, and peer-led “health coach” initiatives. These strategies provide a framework for developing comprehensive prediabetes management interventions aimed at improving self-management ability.Keywords: prediabetic state, patient-centered care, primary prevention, qualitative research